More Effort with Less Pay: On Information Avoidance, Belief Design, and Performance - Nora Szech; Steffen Huck; Lukas Wenner (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
In a tedious real effort task, subjects know that their piece rate is either low or ten times higher. When subjects are informed about their piece rate realization, they adapt their performance. One third of subjects nevertheless forego this instrumental information when given the choice - and perform stunningly well. Agents who are uninformed regarding their piece rate tend to outperform all others, even those who know that their piece rate is high. This also holds for enforced instead of self-selected information avoidance. All our findings can be captured by a model of optimally distorted expectations following Brunnermeier and Parker (2005).
Keywords: D83; D84; J31; 330